Feasibility of gray-blood late gadolinium enhancement evaluation in young patients with congenital and acquired heart disease - Gonzalez de Alba, Cesar; Moghari, Mehdi H.; Browne, Lorna P.; Friesen, Richard M.; Fonseca, Brian; Malone, LaDonna J. (Frontiers in Cardiovascular Medicine, 2023)
Background: Late gadolinium enhancement sequences have become common in pediatric cardiovascular magnetic resonance (CMR) to assess for myocardial fibrosis. Bright-blood late gadolinium enhancement (BB-LGE) by conventional phase sensitive inversion recovery (PSIR) is commonly utilized, but similar T1 value of fibrosis and left ventricular blood pool can make subendocardial areas difficult to assess. A gray-blood LGE (GB-LGE) technique has been described, targeting nulling of the LV blood pool, and demonstrating improvement in ischemic scar detection over BB-LGE in adult patients. We sought to evaluate the feasibility of GB-LGE technique in a young population with congenital and acquired heart disease, and compare its ability to detect subendocardial scar to conventional BB-LGE.Methods: Seventy-six consecutive patients referred for clinical CMR underwent both BB-LGE and GB-LGE on 1.5T and 3T scanners. Conventional PSIR sequences were obtained with TI to null the myocardium (BB-LGE) in short and horizontal long axis stacks. Same PSIR stacks were immediately repeated with TI to null the blood pool (GB-LGE). Both sequences were reviewed separately a week apart by 2 readers, blinded to initial clinical interpretation. Studies were analyzed for overall image quality, confidence in scar detection, confidence in detection of LGE, LGE class, inter and intraobserver agreement for presence of scar, and intraclass correlation coefficient for total scar burden.Results: Overall confidence in myocardial scar detection by BB or GB-LGE as well as grading of image quality were not statistically different; (p = 1 and p = 1) and (p = 0.53, p = 0.18) respectively. There was very good inter-observer agreement for presence of scar on BB-LGE (K = 0.88, 95% CI 0.77-0.99) and GB-LGE (K = 0.84, 95% CI 0.7-0.96), as well as excellent intraobserver agreement for both readers (K = 0.93, 95% CI 0.87-0.99 and K = 0.81 95% CI 0.69-0.95). Interclass correlation coefficient for total scar burden was excellent for BB-LGE (ICC = 0.98, 95% CI 0.96-0.99) and GB-LGE (ICC = 0.94, 95% CI 0.91-0.97).LGE technique is feasible in the pediatric population with congenital and acquired heart disease. It can detect subendocardial/ischemic scar similarly to conventional bright-blood PSIR sequences in the pediatric population.